Design of Rain Water Harvesting Structure for Semi Arid Region (Rajkot, Gujarat, India) - Khandelwal, M K; Shakya, S K; Narda, N K; Khepar, S D (Journal of Agricultural Engineering, 2003)
Daily rainfall and runoff data of 1971-97, collected from Targhedia watershed (Gujarat) was analyzed with relevant statistical tools. A computer programme incorporating hydraulic and hydrological design criteria, and CN method has been developed to design parameters for rain water harvesting structures. The computer program is applied to an existing irrigation tank ’B’ with 4 ha catchment and results of design features (old and new) are compared.